CYTOGENETIC SURVEY OF SOME BRAZILIAN CERAMBYCIDAE (COLEOPTERA, POLYPHAGA, CHRYSOMELIDAE) - Ferreira, A.; Condutta, V. L.; Martins, V. G. (Soc Brasil Genetica, 1993)
Meioformula was determined in 16 species of the family Cerambycidae, seven of them of the subfamily Cerambycinae, eight of Lamiinae and one of Prioninae. Only two species of Cerambycinae and one of Lamiinae showed the basic Polypliaga karyotype (9 + Xy(p)) and the remaining ones showed occurrence of centric fusions and fissions that have modified the basic karyotypes. These results are in accordance with previous studies on other species of this family.